Proceedings of the 11th ACM Conference on Electronic Commerce 2010
DOI: 10.1145/1807342.1807393
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically optimal strategy-proof mechanisms for two-facility games

Abstract: We consider the problem of locating facilities in a metric space to serve a set of selfish agents. The cost of an agent is the distance between her own location and the nearest facility. The social cost is the total cost of the agents. We are interested in designing strategy-proof mechanisms without payment that have a small approximation ratio for social cost. A mechanism is a (possibly randomized) algorithm which maps the locations reported by the agents to the locations of the facilities. A mechanism is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 30 publications
4
122
0
Order By: Relevance
“…The main goal of [30] is the location of a single facility on the real line when agents have single-peaked preferences, and the corresponding bounds shown in Table 1 are from that paper. A series of papers have studied generalizations of the problem to more general metric spaces [1,11,32], multiple facilities [14,23,26,27] or even enhancing strategyproof mechanisms with additional capabilities [21,22]. Most of the related work actually considers the same objectives that we do here, namely the social cost or the maximum cost, with the notable exceptions of the least-squares objective [18], the L p norm of costs [17] or the minimax envy [5].…”
Section: Related Work On Facility Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of [30] is the location of a single facility on the real line when agents have single-peaked preferences, and the corresponding bounds shown in Table 1 are from that paper. A series of papers have studied generalizations of the problem to more general metric spaces [1,11,32], multiple facilities [14,23,26,27] or even enhancing strategyproof mechanisms with additional capabilities [21,22]. Most of the related work actually considers the same objectives that we do here, namely the social cost or the maximum cost, with the notable exceptions of the least-squares objective [18], the L p norm of costs [17] or the minimax envy [5].…”
Section: Related Work On Facility Locationmentioning
confidence: 99%
“…Our primary objective is to explore double-peaked preferences in facility location settings similar to the ones studied extensively for single-peaked preferences throughout the years [1,11,14,18,20,23,26,27,30,32]. For that reason, following the literature we assume that the cost functions are the same for all agents and that the cost increases linearly, at the same rate, as the output moves away from the peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Procaccia and Tennenholtz [17] initiated the study of approximate mechanism design without payments for combinatorial problems by studying facility location problems. Their studies triggered several follow-up articles on this topic (see, e.g., [1,13,12,6,7]). Dughmi and Gosh [4] derived approximate mechanisms without money for several variants of the assignment problems.…”
Section: Binding Reportsmentioning
confidence: 99%
“…The second facility is placed at x j − max{d l , 2d r }, if d l > d r , and to x j + max{d r , 2d l }, otherwise. DICTATORIAL is an adaptation of the mechanism of [10] for the circle. As in [10,Section 5], it can be shown that DICTATORIAL is strategyproof and (n − 1)-approximate for the line.…”
Section: Strategyproof Mechanisms For 2-facility Location: Outlinementioning
confidence: 99%
“…Next, we employ the notion of partial group strategyproofness [10,Section 3], and a new technical tool for moving agents between different coalitions without affecting the mechanism's outcome (Lemma 5.1), and show that any nice mechanism applied to 3-location instances with n ≥ 5 agents either admits a (full) dictator, or places the facilities at the two extremes (Theorem 3.3). Rather surprisingly, this implies that nice mechanisms for 3 agents are somewhat less restricted than nice mechanisms for n ≥ 5 agents.…”
Section: Introductionmentioning
confidence: 99%